2021
DOI: 10.1111/mmi.14830
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids can inhibit Staphylococcus aureus SaeS activity at the membrane independent of alterations in respiration

Abstract: According to the Centers of Disease Control and Prevention (CDC), approximately 2.8 million people in the U.S. are infected by antibiotic-resistant bacteria each year. It is estimated that antibioticresistant Staphylococcus aureus accounted for over 300,000 hospitalizations and over 10,000 deaths in 2017, indicating that S. aureus is a key contributor to the burden of antibiotic-resistant infections (CDC). S. aureus is a Gram-positive bacterium that asymptomatically colonizes 20%-30% of the population, predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Recent publications have uncovered new links between membrane composition and SaeS activation in S. aureus ( 49 , 54 ). Previous work demonstrated that SaeS is inhibited by both saturated and unsaturated straight-chain fatty acids; in contrast, this study reveals BCFAs are activators of SaeS kinase activity in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have uncovered new links between membrane composition and SaeS activation in S. aureus ( 49 , 54 ). Previous work demonstrated that SaeS is inhibited by both saturated and unsaturated straight-chain fatty acids; in contrast, this study reveals BCFAs are activators of SaeS kinase activity in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism provides novel insights into the prevalence of hlb-converting prophages in clinical isolates and the role of the lipid environment in S. aureus adaptation to infection. Incorporation of PUFAs, such as C18:2, into PLs alters crucial functions that interact with the infecting host, including biofilm formation, secretion of virulence factors, and interference with immune defense (8,19,20,(54)(55)(56). Furthermore, C18:2 and sphingolipid metabolism are key pathways affected by S. aureus to decrease macrophage efficacy (57).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, excess levels of both external and cytoplasmic free fatty acids were proposed to modulate bacterial virulence factor production via SaeRS inhibition [ 77 , 78 ]. Unsaturated fatty acids are generally stronger inhibitors than saturated fatty acids [ 79 ]. Accordingly, deletion of respiratory dehydrogenase genes, which leads to altered NAD + /NADH ratios and free fatty acid accumulation, is accompanied by reduced SaeRS activity [ 80 ].…”
Section: Saersmentioning
confidence: 99%
“…Accordingly, deletion of respiratory dehydrogenase genes, which leads to altered NAD + /NADH ratios and free fatty acid accumulation, is accompanied by reduced SaeRS activity [ 80 ]. Fatty acid sensitivity occurs independently of SaePQ but requires the native SaeS transmembrane [ 79 ]. Thus, SaeS probably integrates membrane-active signals to either increase (HPN1) or decrease (fatty acids) SaeS kinase activity.…”
Section: Saersmentioning
confidence: 99%